Metatheatricality of Aristophanes’ comedies in the context of development of European drama - Литовська, Олександра Веніамінівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2019)
Metatheatricality becomes one of the dominants of modern theatre development. Most scholars agree that main feature of metatheatricality is self-reference and that first examples of metatheatre can be found in Ancient Greek drama. The appearance of meta-theatrical elements is directly connected with the formation of one of the principal conflicts of the theatre's inner development – innovation in drama and theater fields was not only rejected, but also ceased to exist with the transition from Old comedy to New one. The comedy used the form of theatrical presentation of the tragedy itself as a "concrete form", but it didn’t mean that comedy was just a parody of a tragedy or tried on her suit, it meant that the drama work was perceived as an independent way of knowing reality. Plays by Aristophanes not only contain multiple examples of drama’s self-reference at the plot and performance level (such plays as “Acharnians”, “Peace”, “Thesmophoriazusae”, “Frogs”), but represent theatrical and historical context for analysis of metatheatrical tendencies in Ancient tragedy. From one hand, metatheatricality of Aristophanes’s comedies became the example for Euripides’s genre shift, from other hand – it was totally abandoned in Menander’s New comedy. Theoretical comprehension of the theatre as an object and subject of art was no longer considered as feature of a play, but became the aim of Aristotelian literary theory. The development of Greek comedy from Aristophanes to Menander represents invariant of European theatre development, where metatheatricality is replaced by artistic credibility and ability for self-reference is replaced by systematised literary critics.